Influence of trust on the acceptance of the RTS,S malaria vaccine in the Kassena-Nankana districts of Ghana - Eustace Bugase; Paulina Tindana (Malaria Journal, 2024)
Abstract Background Vaccines have increasingly become some of the most effective public health tools for promoting health and reducing the burden of infectious diseases. The availability of a malaria vaccine for routine use will be a major milestone, nonetheless, trust by the public for the vaccine could pose a major challenge for its acceptance. Documented evidence such as the boycott of the oral polio vaccine in northern Nigeria and the failure of the Ebola vaccine trial in Ghana among others highlight the impact of public trust on vaccine acceptance. Methods This is an explorative cross-sectional mixed-method study conducted in the Kassena Nankana districts. The study was conducted in the Kassena Nankana Districts between May and December 2020. A total of 390 structured questionnaires were administrated to mothers and caregivers of children under five years of age while 15 in-depth interviews were conducted with mothers and health workers. STATA software Version 16.0 was used to interpret the quantitative data, where bivariate and multivariate regression analysis was performed to determine the influence of trust on vaccine acceptance while QSR NVivo 12 software was used to code the qualitative data to aid the thematic analysis. Results The results revealed that the level of knowledge of the RTS,S vaccine among participants was high. About 95.4% of the mothers had good knowledge of the malaria vaccine and more than half 61.2% of them got information about the vaccine from the health facility. The level of trust for the malaria vaccine was equally high with 91.4% of the mothers reporting that the vaccine treats childhood malaria. In a bivariate analysis, educational status (P = 0.013), ethnicity (P = 0.008), marital status (P = 0.041), education on the vaccine and perceived ineffectiveness P < 0.05, and trust for the malaria vaccine (P < 0.05) were found to be statistically associated with vaccine acceptance. Compared with participants who agree that vaccines are harmless to children, those who disagree ...